The Influence of Foreign Direct Investment (PMA), Inflation, and Money Supply (M2) on the Exchange Rate (IDR/USD) in Indonesia for the Period 2016:Q1-2022:Q4 - Sangadji, Rizka; Maramis, Mauna; Tumangkeng, Steeva (PT FORMOSA CENDEKIA GLOBAL, 2024)
Exchange rates influence economic growth by comparing a country's currency with other currencies. In a globalized world, currency exchange rates linked to monetary policy worry businesses and governments. This research examines how M2, inflation, and FDI influence the Indonesian exchange rate simultaneously and differently. This research uses multiple linear regression. The research results show that inflation and M2 (money supply) have a positive and significant effect on the exchange rate. Foreign Direct Investment (PMA) is somewhat detrimental and has a significant impact. Then, M2, inflation, and FDI all influence the exchange rate simultaneously. This research uses quantitative data research. This research uses secondary time series data from 2016:Q1 to 2022:Q4. Inflation, PMA, M2, and currency exchange rates are used in this research.